The Progress of Therapeutic Vaccination with Regard to Tuberculosis - Cardona, Pere-Joan (Frontiers in Microbiology, 2016)
A major problem with tuberculosis (TB) control is the long duration of drug therapy –both for latent and for active TB. Therapeutic vaccination has been postulated to improve this situation, and to this end there are several candidates already in clinical phases of development. These candidates follow two main designs, namely bacilli-directed therapy based on inactivated -whole or -fragmented bacillus (Mycobacterium w and RUTI) or fusion proteins that integrate non-replicating bacilli -related antigens (H56 vaccine), and host-directed therapy to reduce the tissue destruction. The administration of inactivated Mycobacterium vaccae prevents the “Koch phenomenon” response, and oral administration of heat-killed Mycobacterium manresensis prevents excessive neutrophilic infiltration of the lesions. This review also tries to explain the success of Mycobacterium tuberculosis by reviewing its evolution from infection to disease, and highlights the lack of a definitive understanding of the natural history of TB pathology and the need to improve our knowledge on TB immunology and pathogenesis.